2012
DOI: 10.1371/journal.pone.0030916
|View full text |Cite|
|
Sign up to set email alerts
|

Dilated Thin-Walled Blood and Lymphatic Vessels in Human Endometrium: A Potential Role for VEGF-D in Progestin-Induced Break-Through Bleeding

Abstract: Progestins provide safe, effective and cheap options for contraception as well as the treatment of a variety of gynaecological disorders. Episodes of irregular endometrial bleeding or breakthrough bleeding (BTB) are a major unwanted side effect of progestin treatment, such that BTB is the leading cause for discontinued use of an otherwise effective and popular medication. The cellular mechanisms leading to BTB are poorly understood. In this study, we make the novel finding that the large, dilated, thin walled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
12
1
3
Order By: Relevance
“…In women treated with progestin prior to hysterectomy for heavy menstrual bleeding, podoplanin-positive lymphatic vessels were enlarged in the endometrium compared to controls (Fig. 16) (277). …”
Section: Organization and Anatomy Of The Lymphatic Systemmentioning
confidence: 99%
“…In women treated with progestin prior to hysterectomy for heavy menstrual bleeding, podoplanin-positive lymphatic vessels were enlarged in the endometrium compared to controls (Fig. 16) (277). …”
Section: Organization and Anatomy Of The Lymphatic Systemmentioning
confidence: 99%
“…Arteries/arterioles drain into the corresponding venous system: the spiral artery/arterioles in the functionalis drain into capillary plexus which subsequently drain into venous lakes. Thus, all spinal arteries in the functionalis eventually drain into the draining venous vessels in the functionalis whereas straight arteries drain into the venous vessels in the basalis [29]- [31]. As mentioned above, all arterial, capillary plexus, venous and lymphatic vessels undergo menstrual cyclic changes and disintegrate for the menstrual bleeding.…”
Section: Discussionmentioning
confidence: 95%
“…In the late-secretory phase, when estradiol and progesterone levels decline, blood flow in the functionalis declines. Dilated lymphatic and venous vessels characteristically appear at the premenstrual phase, and this thin-walled lymphatic and venous vessels are also observed in progestin-induced break-through bleeding [26]- [29]. By functional study using mouse models, Rodgers et al reported that menstrual bleeding commences from the wall of an arterial or capillary vessels once previously constricted spiral arteries relax and blood flow recommences, which is responsible for 70% of blood loss [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of epidermal thickness 34, collagen index 35, and microvessels, hair follicles and cell counting 36-38 in high-power field (HPF) were performed with ImageJ software. The vessel area, which is defined as the sum of all vessel segments/HPF, was quantified by ImageJ using the technique described previously 39. Five stained sections in each group for each time point were visualized using an Olympus IX71 microscopy, and three random views in each section were selected for quantitative assay.…”
Section: Methodsmentioning
confidence: 99%